A model problem concerning the ionic transport in microstructured solid electrolytes - Curto Sillamoni, Ignacio José (2014)
We consider ionic transport by diffusion and migration through microstructured solid electrolytes. The effective response is determined by homogenizing the relevant field equations via the notion of multi-scale convergence. The theory is applied to semi-crystalline polymer electrolytes with spherulitic morphologies. Predictions support recent experimental observations on doped poly-ethylene-oxide (PEO) systems which suggest that the anisotropic crystalline phase can actually support faster ion transport than the amorphous phase along certain directions dictated by the morphology of the polymeric chains.